Evolution of Infantile Spasms to Lennox-Gastaut Syndrome: What Is There to Know?. (August 2021) - Nelson, Julie A.; Demarest, Scott; Thomas, Jake; Juarez-Colunga, Elizabeth; Knupp, Kelly G.
Objective: Children with infantile spasms may develop Lennox-Gastaut syndrome. The diagnostic criteria for Lennox-Gastaut syndrome are vague, and many experts use varying combinations of the following criteria for diagnosis: paroxysmal fast activity on electroencephalography (EEG), slow spike and wave on EEG, developmental delay, multiple seizure types, and nocturnal tonic seizures. Our objective was to determine the prevalence of Lennox-Gastaut syndrome in a high-risk cohort of children with a history of infantile spasms and the characteristics of infantile spasms that were associated with the diagnosis of Lennox-Gastaut syndrome. Methods: Children with infantile spasms who were diagnosed and treated at Children's Hospital Colorado between 2012 and 2018 were included. Lennox-Gastaut syndrome was defined as having 3 of 5 of the following characteristics: paroxysmal fast activity, slow spike and wave, current developmental delay, multiple seizure types, or tonic seizures. Descriptive statistics were performed using median and interquartile range. Univariable analysis was performed with Pearson chi-square, Fisher exact, or the Kruskal-Wallis test. Results: Ninety-seven children met inclusion criteria, and 36% (35/97) met criteria for Lennox-Gastaut syndrome. Developmental delay and history of seizures prior to the onset of infantile spasms were identified as risk factors for the development of Lennox-Gastaut syndrome ( P = .003) as was poor response to first treatment for spasms ( P = .004). Children with an unknown etiology of infantile spasms were less likely to develop Lennox-Gastaut syndrome ( P = .019). Eighty percent (28/35) of the children who met Lennox-Gastaut syndrome criteria lacked a documented diagnosis. Conclusions: Thirty-six percent of children with infantile spasms met criteria for Lennox-Gastaut syndrome. Risk factors for development of Lennox-Gastaut syndrome were developmental delay and seizures prior to the onset of infantile spasms and poor response to first treatment for infantile spasms. Children with an unknown etiology of infantile spasms were less likely to develop Lennox-Gastaut syndrome. Eighty percent of the children who met our criteria were not given a documented diagnosis of Lennox-Gastaut syndrome, which highlights the fact that many children may not be receiving a diagnosis of Lennox-Gastaut syndrome. We recommend establishing clear guidelines for the diagnosis of Lennox-Gastaut syndrome to ensure that the diagnosis is being made accurately.